Avant-Garde Fascism : The Mobilization of Myth, Art, and Culture in France, 1909-1939 - Antliff, Mark, 1957- (Book collections on Project MUSE., 2007)
An investigation of the central role that theories of the visual arts and creativity played in the development of fascism in France between 1909 and 1939.